Qur'anic Studies: Ber-Ushul Fiqh dengan Maqashid Syariah Sebagai Metode dalam Perspektif Yudian Wahyudi - S Sadari (SHAHIH: Journal of Islamicate Multidisciplinary, 2018)
This article offers the maqasyid as 'method' rather than 'doctrine', method is a process of developmental dynamics, whereas doctrine is a stalled idea of development. The findings are productivity of thinking that can be accounted scientifically both quantity and quality. Its usul fiqh literary ground "back to al-Qur'an and as-Sunnah" is the best choice of Islamic repertoire. Making ushul fiqh with maqasyid as 'method' will reject the Western slogan of hermeneutics. The perspective of ushul fiqh Yudian Wahyudi regretted that scholars who study Islam in the West, have experienced alienation with ushul fiqh because it is not well understood, then want to replace it with hermeneutics whereas hermeneutics are understood still "periphery", this will weaken the authority of revelation as source Islam. The epistemological plea of Yudian is to realize that hermeneutics when applied to the Qur'an is a big mistake, recognizing that hermeneutics criticizing ushul fiqh is an upside-down and superficial epistemology, so how to treat it is by historical, thematic, reflective, analytical, comparative Islamic and critical.